Kompleks Praseodimium Ditiokarbamat 1,10 Fenantrolin - Ibrahim Baba,; Indah Raya, (Universiti Kebangsaan Malaysia, 2010)
Seven promethium (Pr) complexes with 1,10-phenantroline were successfully synthesized using in situ methods from the reactions of eight amines with praseodymium(III) salts together with carbon disulphide. Methatesis and condensation were the most successful methods to prepare praseodymium dithiocarbamate 1,10-phenantroline complexes with general formula Pr[S2CNR1R2]3phen (R1 = ethyl, methyl; R2 = butyl, heptyl, isopropyl, isobutyl, benzyl and cyclohexyl; phen= 1,10-phenantroline). These complexes were characterized using elemental analysis, infrared, thermogravimetric analysis and conductivity. Microelemental analysis data were in agreement with the general formula. Infrared spectra of complexes showed the thioureide ν(C-N) bands were in the region of 1454 - 1484 cm-1 and ν(C-H) bands in the region of 2853-2973 cm-1. The single ν(C-S) bands appeared in the region of 959 – 999 cm-1 has proved to be bidentate bonding. The 13C NMR spectroscopic data for these complexes showed that the carbon signal from NCS2 moiety were in the range of 192 – 212 ppm. The crystal structure of Pr[S2CN(CH3)(C7H7)]3phen adopts triclinic system (space group Pī) with a distorted dodecahedron geometry with a = 10.7165(16) A , b = 12.2897(19) A, c = 16.586(2) A, α = 73.887(2)o, β = 74.879(2)o and γ = 71.837(2)o and Z = 2. Three dithiocarbamates and one phenanthroline ligands were coordinated to the central Pr atom in bidentate manner.